Probability & statistics for engineers & scientists - Walpole, Ronald E.; Myers, Raymond H.; Myers, Sharon L.; Ye, Keying (Pearson Education Limited, 2016)
For junior/senior undergraduates taking probability and statistics as applied to engineering, science, or computer science. This classic text provides a rigorous introduction to basic probability theory and statistical inference, with a unique balance between theory and methodology. Interesting, relevant applications use real data from actual studies, showing how the concepts and methods can be used to solve problems in the field. This revision focuses on improved clarity and deeper understanding. This latest edition is also available in as an enhanced Pearson eText